EVALUATION OF VITAMIN D IN MOTHERS AND NEWBORNS AT BIRTH IN SULAIMANI MATERNITY TEACHING HOSPITAL - Mahmood, Diya Yousif; Noori, Saman Hussein (Journal of Sulaimani Medical College, 2025)
Background Deficiencies in vitamin D are frequent worldwide. Approximately 1 billion individuals around the globe are vitamin D deficient (<20ng/ml), and half of the population is insufficient (20-29ng/ml). According to extensive epidemiological studies, vitamin D deficiency is common in women, particularly pregnant and nursing mothers. Vitamin D deficiency during pregnancy is associated with various maternal and fetal health effects.. Objectives Vitamin D levels in fetuses and newborns are directly related to their mothers’ levels during pregnancy. The study aims to assess and compare the vitamin D levels of mothers and their newborn babies. Additionally, we are interested in determining whether there is a link between vitamin D levels and delivery outcomes. Patients and Methods One hundred pairs of mothers and newborns enrolled in a cross-sectional study at Maternity Teaching Hospital in Sulaimani. Any newborn baby diagnosed with a congenital abnormality during pregnancy was excluded. Also, any mother that was on anticonvulsant drugs was excluded. Blood samples for vitamin D analysis were taken from the mothers and newborns at birth. In addition, the demographic and medical data of the mothers and newborns were recorded. All evaluations had a p-value of 0.05 as the threshold for statistical significance. Results The mothers’ and newborns’ mean vitamin D were 17.2±13.33 ng/ml and 10.48±9.77 ng/ml, respectively. An examination of the data using statistical methods indicated a connection between the vitamin D found in mothers and the levels found in their newborns (p-value=0.001). Furthermore, higher levels during pregnancy were linked to better Apgar scores (≥7) for their newborn children (p-value=0.03). Maternal vitamin D level was not statistically associated with other birth outcomes; p-value > 0.05. Conclusion The results of this study show that vitamin D deficiency in mothers leads to deficiency in their newborns. Except for the Apgar score, no statistically significant relationship was found between maternal vitamin D levels and other birth outcomes.
Keywords: Vitamin D; Pregnancy; Vitamin D deficiency; Birth weight; Preterm birth; Apgar score